ANALISIS DATA KUALITATIF DALAM PENELITIAN TEKNIK ARSITEKTUR - Sumarjo H (Universitas Negeri Yogyakarta, 2010)
The map of research in architectural field has a wide complexity, requiresqualitative and/or quantitative analysis method. Until now, the analysis of qualitative’s data model in architectural engineering is varied and not yet sistematically. This is frequently lead to the question about analysis technique, interpretation and conceptualization of research findings. This article’s aim is to asses the sistematic way on the qualitative’s data analysis in architectural research. The main parts of qualitative research are: (1) data, (2) analysis procedure and interpretation and (3) report.Analysis procedure and interpretation through coding is separated into open coding and axial coding. Open coding is detail process, practice, comparation,conceptualization and data categorize on the dimension properties. Open coding is part of analysis which is particularly deal with naming and fenomena categorizing through data testing. Axial coding is a set of procedure which are arranged with a new way after open coding with the form of code consist of: condition, size, context, strategy and consequence. The appropriate qualitative’s data analysis for architectural research are: (1) the study of a shape modification’s effect caused by the change of socio-culture environment, (2) the research to find a new point of view (exploration) in architecture field, (3) the research to revealed the meaning behind the change of phenomenon dueto it basic socio-culture, and (4) the reseach tha requires in-depth review.Keywords: architectural research, qualitative data analysis